PREVENT THE RISK OF SUICIDE IN ADOLESCENTS IN CRISIS SITUATIONS PSYCHOLOGICAL MECHANISMS OF ACQUISITION (ResearchJet Journal of Analysis and Inventions, 2021)
This article discusses the theoretical and practical approaches of psychologists to the crisis situations observed during adolescence, as well as the psychological significance of the judicial risks that can be observed in adolescents.